2017
DOI: 10.4314/ijest.v9i1.2
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of multi-response dynamic systems integrating multiple regression and Taguchi’s dynamic signal-to-noise ratio concept

Abstract: The principal difference between a dynamic and a static system is that the former includes a signal factor for expressing the intended output while the later does not. Assuming a linear association exists between the response and signal variables, Taguchi offered a two-stage route for optimizing a dynamic system: maximize the dynamic signal-to noise ratio (DSN) and then, change the gradient to the desired gradient by a suitable modification parameter. Some researchers have indicated limitations to Taguchi's DS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
(101 reference statements)
0
5
0
Order By: Relevance
“…Pal & Gauri [17] proposed the use of multiple regression and the Taguchi SNR applied to the RPD for dynamic characteristics. Fang et al [18] applied optimization techniques for multi-objective DRP in the analysis of fatigue in truck cabins.…”
Section: Multi-objective Optimization In Rpdmentioning
confidence: 99%
See 1 more Smart Citation
“…Pal & Gauri [17] proposed the use of multiple regression and the Taguchi SNR applied to the RPD for dynamic characteristics. Fang et al [18] applied optimization techniques for multi-objective DRP in the analysis of fatigue in truck cabins.…”
Section: Multi-objective Optimization In Rpdmentioning
confidence: 99%
“…From the previous model, the models for the mean in eq are defined. (17) and the variance in eq. (18).…”
Section: Determination Of the Modelsmentioning
confidence: 99%
“…The study can determine the optimal levels of the controllable design parameters in a continuous space and allows for increasing robustness in the dynamic Taguchi method. Pal and Gauri (2017) develope a procedure, which uses the multi-regression (MR) technique and the Taguchi dynamic S/N ratio (DSN) to optimize the multi-response dynamic systems. First, the multiple regression equations for the dynamic system are fitted based on the sample data, then, the dynamic S/N ratio (known as MRDSN) for the different response variables is calculated based on the multiple regression values.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results have shown that the MRWSN method is superior to the CDF method in terms of optimization performance. Pal and Gauri (2018) revise the MRDSN method (Pal and Gauri, 2017) by introducing a new performance metric called weighted predicted response-based S/N ratio (WPRSNR). The experimental findings have shown that the modified MRDSN method outperforms the MRDSN procedure in searching the optimal design solution with respect to the total S/N and the MSE of the individual responses.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hsieh et al [16] applied artificial neural network to the problem of multi-response optimization in RPD. Pal and Gauri [17] presented using multiple regression and the Taguchi signal-to-noise ratio to robust parameter design the event of dynamic characteristics. Fang et al [18] studied the analysis of fatigue in truck cabins with respect to multi-response optimization based robust parameter design.…”
Section: Introductionmentioning
confidence: 99%